Cervical cancer screening in low-income countries: a report on the implementation of cervical screening in Luzon, Philippines - Samantha Carr; Charlotte Hespe (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Cervical cancer is the second leading cause of cancer death among women in the Philippines. This study is the first clinical audit of a cervical cancer screening program in a socioeconomically deprived community in rural Philippines. The aim of this study was to quantify the proportion of women screened who were identified as having no cervical abnormality, low-grade squamous intraepithelial lesion (LSIL/CIN 1), high grade squamous intraepithelial lesion (HSIL/CIN 2) or carcinoma in situ (CIS) and to measure the proportion of women who received appropriate follow-up. # Methods Retrospective audit of data from medical records collected between 2013-2017 in Santo Tomas, Luzon, Philippines. # Results 625 women presented for screening and 615 satisfactory screening tests were conducted. 88.4% of women had a normal result (95% confidence interval, CI=85.8-90.9), 10.2% had low-grade changes (95% CI=7.8-12.6), 0.3 % had high-grade changes (95% CI=0.0-1.0) and 0.5% were diagnosed with cervical cancer (95% CI=0.0-1.0). Follow-up was poor for women with normal (26.1%; 95% CI=21.6-31.1) and abnormal (27.1%; 95% CI=15.3-41.8) results. # Conclusions Our experience confirms previous studies surrounding barriers to follow up and treatment within developing countries and should be complemented with qualitative research to further explore these barriers. Given low rates of follow-up, a screen-and-treat approach and/or human papilloma virus (HPV) vaccination may be more appropriate within this community.